Penataan Lingkungan Tukad Bindu di Kota Denpasar; Mengubah Resem Menjadi Kenyem - Mudra, I Ketut; Bharuna S, Anak Agung Gde Djaja; Aritama, Anak Agung Ngurah (Jurnal Arsitektur Universitas Udayana, 2025)
The Tukad (River) Bindu is one of the many rivers in the Denpasar City area, which initially had problems with cleanliness and waste as the main obstacles. Since it was laid out in 2010, the condition of the river environment, which was initially resem (dirty; slum) has changed to kenyem (smile). This article will describe changes in the Tukad Bindu environment after structuring activities were carried out. This qualitative research, designed using a descriptive method, discusses three things, namely: (1) the condition and use of the Tukad Bindu environment before the arrangement; (2) the form of arrangement and management of the Tukad Bindu environment; and (3) the condition and use of the Tukad Bindu environment after arrangement. The results and discussions found that before the restructuring was carried out, the environmental conditions of Tukad Bindu were very dirty, filthy and rundown because they were used by the local community as a place to dump rubbish, household waste and human waste. The management and arrangement of rivers carried out by the Tukad Bindu Foundation has been able to change the condition of the river environment to make it clean and neatly arranged. The community enthusiastically uses the recreation and sports facilities provided by the foundation. The religious ritual procession "murwa daksina" which uses the footpath along the banks of Tukad Bindu, shows high appreciation and commitment in preserving the river as a water resource. Keywords: arrangement, environmental conditions, utilization, Tukad Bindu